DEVELOPING LEARNING INSTRUMENTS BASED ON EXPERIENTIAL LEARNING MODEL ON SUBJECT OF CIRCLE FOR 8th GRADE STUDENTS OF JUNIOR HIGH SCHOOL - Anggi Mihardi; Titi Solfitri (Jurnal Prinsip Pendidikan Matematika, 2021)
The purpose of this research is to develop the mathematics learning instrument: syllabus, lesson plans (RPP), and student worksheets (LKPD) using the experiential learning model on circle subject for 8th grade students of junior high school (SMP) that is categorized as valid and categorized as practical. This research used Research and Development (R&D) model with ADDIE procedure; analyze, design, development, implementation, and evaluation. The research instruments that used in this research were learning instrument validation sheets and student response questionnaires. Syllabus, RPP, and LKPD validated by 3 validators and revised according to suggestion from validator. The valid LKPD then tested in two stages, the small group trial and large group trial. According to the result of validation data analysis of learning instruments, those were categorized as very valid with the average score for syllabus was 4.24, for RPP was 4.18, and LKPD was 3,85. According to the result of student response questionnaires toward the LKPD practicality already the requirements of practicality with the percentage of students' response reaches 84% in large group trials. According to the result of data analysis and the discussion, it can be concluded that the learning instruments using the experiential learning model on circle subject were very valid, and the LKPD were very practical to be used by 8th grade students of junior high school.